DESIGN OF COGNITIVE FORMATION TECHNOLOGY INDEPENDENCES OF HIGH SCHOOL STUDENTS IN THE STUDY OF ECONOMIC DISCIPLINES (Pedagogy of Higher and Secondary Education, 2010)
The article reveals some approaches concerning forming students cognitive independence in the course of economic disciplines training, special attention is paid to working out the technology, and also to organizational forms, methods, receptions and means as its integral components.
Keywords: independence; cognitive independence; forms; methods and receptions in economic disciplines training